PROFILE OF CAREER DECISION MAKING DIFFICULTIES OF UPPER MIDDLE STUDENTS - daffa ikhsan daffa ikhsan nurpajari kusmana (Psikoeduko: Jurnal Psikologi Edukasi dan Konseling, 2024)
This research aims to determine the profile of difficulties in career decision making among high school students at Singaparna 1 Public High School. This descriptive research was conducted at SMA Negeri 1 Singaparna which is located in Tasikmalaya district. The measuring tool used is a questionnaire on students' career-making difficulties which is directly adapted. The research results show that the criteria for difficulty in making career decisions are categorized as high, medium and low. With a total of 432 students as respondents, 314 respondents were in the high categorization with a percentage of 73%, 118 respondents were in the medium categorization with a percentage of 27%, and there were no respondents in the low categorization. With three aspects, namely Lack of Readiness, Lack of Information (lack of information) and Inconsistent Information (inconsistent information). Furthermore, the profile of difficulty in making career decisions is seen from gender, showing a Sig result of 0.97 0.05, which means there is no difference between the difficulty of making career decisions for men and women in class XI students at SMA Negeri 1 Singaparna. Lack of career decision making among class XI students is relatively high, so there are still many students who cannot make career decisions, still feel confused, don't know their talents and interests, and lack career information.